P131 Role of cryoprotectants and seminal plasma in the fertility of cooled-stored donkey (Equus asinus) semen - A.C. Silva; C.Z. dos Santos; M. Marchetti; H. Hitson; R. Almeida; F.P. Lisboa; G.A. Monteiro; M.A. Alvarenga; L. Segabinazzi (Journal of Equine Veterinary Science, 2026)

New palynostratigraphic data from the Kungurian (Cisuralian) Guncina Formation, Athesian District (Southern Alps, northern Italy) with regional-global correlation - Amalia Spina; Lorenzo Marchetti; José B. Diez; Enrico Capezzuoli; Haidra Saleh; Iván R. Barreiro; Evelyn Kustatscher; Ausonio Ronchi (Journal of Iberian Geology, 2026)

An evaluation of the utility of blood concentration of somatic mutagens to inform germ cell mutagenic hazard - Roger Godschalk; Bente Brauwers; Connie L. Chen; Raffaella Corvi; Kerry L. Dearfield; George R. Douglas; Naveed Honarvar; David Kirkland; Frank Le Curieux; Ann-Karin Olsen; Stefan Pfuhler; Leon F. Stankowski; et al. (Regulatory Toxicology and Pharmacology, 2026)

Palynological assemblages from the 2nd tectono-sedimentary cycle of the Southern Alps: New constraints for the onset of the Alpine cycle and regional-global inferences - A. Spina; E. Capezzuoli; N. Gretter; L. Marchetti; C. Corradini; N. Degl'Innocenti; R. Scarani; A. Ronchi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Temporal analyses of germ cell mutations using the MutaMouse model support the recommended design in OECD test guideline 488 - Gu Zhou; Andrew Williams; Danielle P. M. LeBlanc; George R. Douglas; Carole L. Yauk; Francesco Marchetti (Archives of Toxicology, 2025)
The Organisation for Economic Co-operation and Development test guideline (TG) 488 uses transgenic rodent models to assess in vivo mutagenesis. TG 488 recommends 28 consecutive days of exposure with sampling of germ cells from seminiferous tubules 28 days post-exposure (i.e., 28 + 28d). We analyzed mutant frequencies (MF) in male germ cells up to 70 days post-exposure to determine whether designs other than 28 + 28d are necessary for assessing germ cell mutagenicity. Adult MutaMouse males received various doses of benzo(a)pyrene (BaP), N -ethyl- N -nitrosourea (ENU), isopropyl methanesulfonate (iPMS), or procarbazine (PRC) alongside vehicle controls for 28 days orally. Germ cells were collected from seminiferous tubules at + 3d, + 28d, + 42d, or + 70d post-exposure and MF quantified using the lacZ assay. Significant increases in lacZ MF were observed for all four chemicals at 28 + 28d. No further increases occurred at later sampling times. There was no significant effect with BaP at 28 + 3d, and a significantly stronger response with ENU and BaP at 28 + 28d compared to 28 + 3d. PRC produced the strongest response at 28 + 3d, while there was no impact of different sampling times for iPMS. Both these chemicals significantly reduced testis weight at 28 + 3d and 28 + 28d. Finally, benchmark dose modeling generated overlapping confidence intervals among the four sampling times for ENU, iPMS, and PRC. However, for BaP, the confidence interval was significantly greater at 28 + 3d than at the other sampling times. These results support the use of the 28 + 28d design as the recommended experimental design for germ cells in TG 488 and that later sampling times are not necessary.

Comparison of submerged and air liquid interface exposure: limitations and differences in the toxicological effects evaluated in bronchial epithelial cells - Y. Allouche; S. Marchetti; R. Bengalli; G. Motta; L. Pagliarulo; F. Cazier; S. Achard; M. Fadel; P. Mantecca; D. Courcot; F. Ledoux; A. Verdin; et al. (Environmental Research, 2025)

Corrigendum: Diatom transcriptional and physiological responses to changes in iron bioavailability across ocean provinces - Natalie R. Cohen; Kelsey A. Ellis; Robert H. Lampe; Heather McNair; Benjamin S. Twining; Maria T. Maldonado; Mark A. Brzezinski; Fedor I. Kuzminov; Kimberlee Thamatrakoln; Claire P. Till; Kenneth W. Bruland; William G. Sunda; et al. (Frontiers in Marine Science, 2025)

Inhalation of nanoplastics in the mouse model: Tissue bio-distribution and effects on the olfactory system - G. Prosperi; N. Marchetti; A. D'Elia; R. Massari; M. Giusto; A. Pietrodangelo; T. Rossi; A. Nucara; F. Scavizzi; G. Strimpakos; S. Marinelli; S. Mandillo; et al. (Science of The Total Environment, 2025)

Alkali, thermal, or thermo-alkali pre-treatment to improve the anaerobic digestion of poly(lactic acid)? - C. Vasmara; G. Cazaudehore; E. Ceotto; R. Marchetti; C. Sambusiti; F. Monlau (Water Research, 2024)

Microbial respiration in contrasting ocean provinces via high-frequency optode assays - Melanie R. Cohn; Brandon M. Stephens; Meredith G. Meyer; Garrett Sharpe; Alexandria K. Niebergall; Jason R. Graff; Nicolas Cassar; Adrian Marchetti; Craig A. Carlson; Scott M. Gifford (Frontiers in Marine Science, 2024)
Microbial respiration is a critical component of the marine carbon cycle, determining the proportion of fixed carbon that is subject to remineralization as opposed to being available for export to the ocean depths. Despite its importance, methodological constraints have led to an inadequate understanding of this process, especially in low-activity oligotrophic and mesopelagic regions. Here, we quantify respiration rates as low as 0.2 µ mol O 2 L -1 d -1 in contrasting ocean productivity provinces using oxygen optode sensors to identify size-fractionated respiration trends. In the low productivity region of the North Pacific Ocean at Station Papa, surface whole water microbial respiration was relatively stable at 1.2 µ mol O 2 L -1 d -1 . Below the surface, there was a decoupling between respiration and bacterial production that coincided with increased phytodetritus and small phytoplankton. Size-fractionated analysis revealed that cells <5 µ m were responsible for the majority of the respiration in the Pacific, both at the surface and below the mixed layer. At the North Atlantic Porcupine Abyssal Plain, surface whole water microbial respiration was higher (1.7 µ mol O 2 L -1 d -1 ) than in the Pacific and decreased by 3-fold below the euphotic zone. The Atlantic size-fraction contributions to total respiration shifted on the order of days during the evolution of a phytoplankton bloom with regular storm disturbances. The high-resolution optode method used in the Atlantic captured these significant shifts and is consistent with coinciding stain-based respiration methods and historical site estimates. This study highlights the dynamic nature of respiration across vertical, temporal, and size-fractionated factors, emphasizing the need for sensitive, high-throughput techniques to better understand ocean ecosystem metabolism.

A second update to the checklist of the vascular flora native to Italy - F. Bartolucci; L. Peruzzi; G. Galasso; A. Alessandrini; N. M. G. Ardenghi; G. Bacchetta; E. Banfi; G. Barberis; L. Bernardo; D. Bouvet; M. Bovio; G. Calvia; et al. (Plant Biosystems, 2024)

A second update to the checklist of the vascular flora alien to Italy - G. Galasso; F. Conti; L. Peruzzi; A. Alessandrini; N. M. G. Ardenghi; G. Bacchetta; E. Banfi; G. Barberis; L. Bernardo; D. Bouvet; M. Bovio; M. Castello; et al. (Plant Biosystems, 2024)

Error-corrected next generation sequencing – Promises and challenges for genotoxicity and cancer risk assessment - Francesco Marchetti; Renato Cardoso; Connie L. Chen; George R. Douglas; Joanne Elloway; Patricia A. Escobar; Tod Harper; Robert H. Heflich; Darren Kidd; Anthony M. Lynch; Meagan B. Myers; Barbara L. Parsons; et al. (Mutation Research - Reviews in Mutation Research, 2023)

Invasive frogs show persistent physiological differences to elevation and acclimate to colder temperatures - Jack R. Marchetti; Karen H. Beard; Emily E. Virgin; Erin L. Lewis; Steven C. Hess; Kwanho C. Ki; Layne O. Sermersheim; Adriana P. Furtado; Susannah S. French (Journal of Thermal Biology, 2023)

Investigation of HER2 gene amplification and protein expression in canine primary pulmonary carcinoma - B. Brunetti; R. Marchetti; F. Millanta; G. Tura; L.V. Muscatello; E. Di Oto; E.L. Laddaga; A. De Leo; G. Tallini; B. Bacci (Journal of Comparative Pathology, 2023)

Evaluation of a long-term information tool reveals continued suitability for identifying bycatch hotspots but little effect on fisher location choice - Zachary A. Siders; Robert N.M. Ahrens; Summer Martin; Edward V. Camp; Alexander R. Gaos; John H. Wang; Jamie Marchetti; T. Todd Jones (Biological Conservation, 2023)

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

The 28 + 28 day design is an effective sampling time for analyzing mutant frequencies in rapidly proliferating tissues of MutaMouse animals - Francesco Marchetti; Gu Zhou; Danielle LeBlanc; Paul A. White; Andrew Williams; Carole L. Yauk; George R. Douglas (Archives of Toxicology, 2021)
The Organisation for Economic Co-Operation and Development Test Guideline 488 (TG 488) uses transgenic rodent models to generate in vivo mutagenesis data for regulatory submission. The recommended design in TG 488, 28 consecutive daily exposures with tissue sampling three days later (28 + 3d), is optimized for rapidly proliferating tissues such as bone marrow (BM). A sampling time of 28 days (28 + 28d) is considered more appropriate for slowly proliferating tissues (e.g., liver) and male germ cells. We evaluated the impact of the sampling time on mutant frequencies (MF) in the BM of MutaMouse males exposed for 28 days to benzo[a]pyrene (BaP), procarbazine ( PRC), isopropyl methanesulfonate (iPMS), or triethylenemelamine (TEM) in dose–response studies. BM samples were collected + 3d, + 28d, + 42d or + 70d post exposure and MF quantified using the lacZ assay. All chemicals significantly increased MF with maximum fold increases at 28 + 3d of 162.9, 6.6, 4.7 and 2.8 for BaP, PRC, iPMS and TEM, respectively. MF were relatively stable over the time period investigated, although they were significantly increased only at 28 + 3d and 28 + 28d for TEM. Benchmark dose (BMD) modelling generated overlapping BMD confidence intervals among the four sampling times for each chemical. These results demonstrate that the sampling time does not affect the detection of mutations for strong mutagens. However, for mutagens that produce small increases in MF, sampling times greater than 28 days may produce false-negative results. Thus, the 28 + 28d protocol represents a unifying protocol for simultaneously assessing mutations in rapidly and slowly proliferating somatic tissues and male germ cells.

Population Pharmacokinetics of Intracellular 5-Fluorouridine 5′-Triphosphate and its Relationship with Hand-and-Foot Syndrome in Patients Treated with Capecitabine - Julie M. Janssen; Bart A. W. Jacobs; Jeroen Roosendaal; Ellen J. B. Derissen; Serena Marchetti; Jos H. Beijnen; Alwin D. R. Huitema; Thomas P. C. Dorlo (The AAPS Journal, 2021)

Efficient zinc/cobalt inter‐replacement in northeast Pacific diatoms and relationship to high surface dissolved Co : Zn ratios - Riss M. Kellogg; Matthew R. McIlvin; Jagruti Vedamati; Benjamin S. Twining; James W. Moffett; Adrian Marchetti; Dawn M. Moran; Mak A. Saito (Limnology and Oceanography, 2020)
The importance of zinc (Zn) as a nutrient and its ability to be substituted for by cobalt (Co) have been characterized in model marine diatoms. However, the extent to which this substitution capability is distributed among diatom taxa is unknown. Zn/Co metabolic substitution was assayed in four diatom species as measured by the effect of free ion concentrations of Zn 2+ and Co 2+ on specific growth rate. Analysis of growth responses found substitution of these metals can occur within the northwest Atlantic isolate Thalassiosira pseudonana CCMP1335, the northeast Atlantic isolate Phaeodactylum tricornutum CCMP632, and within the northeast Pacific isolates Pseudo‐nitzschia delicatissima UNC1205 and Thalassiosira sp. UNC1203. Metabolic substitution of Co in place of Zn in the Atlantic diatoms supports their growth in media lacking added Zn, but at the cost of reduced growth rates. In contrast, highly efficient Zn/Co substitution that supported growth even in media lacking added Zn was observed in the northeast Pacific diatoms. We also present new data from the northeast Pacific Line P transect that revealed dissolved Co and Zn ratios (dCo : dZn) as high as 3.52 : 1 at surface (0–100 m) depths. We posit that the enhanced ability of the NE Pacific diatoms to grow using Co is an adaptation to these high surface dCo : dZn ratios. Particulate metal data and single‐cell metal quotas also suggest a high Zn demand in diatoms that may be partially compensated for by Co.

Interannual radial growth sensitivity to climatic variations and extreme events in mixed-species and pure forest stands of silver fir and European beech in the Italian Peninsula - S. Versace; D. Gianelle; V. Garfì; G. Battipaglia; F. Lombardi; M. Marchetti; R. Tognetti (European Journal of Forest Research, 2020)

Interactive effects of iron and light limitation on the molecular physiology of the Southern Ocean diatom Fragilariopsis kerguelensis - Carly M. Moreno; Weida Gong; Natalie R. Cohen; Kimberly DeLong; Adrian Marchetti (Limnology and Oceanography, 2020)
The polar diatom Fragilariopsis kerguelensis is ubiquitous in Southern Ocean waters and is a major responder to iron fertilization, encountering large gradients in iron concentrations and light availability. We performed a comparative transcriptomic analysis of F. kerguelensis grown under varying iron and light conditions in order to investigate the molecular underpinnings that may explain its physiological response to iron and light limitation. Low iron reduced growth rates more than low light, but there was not an additive effect of low iron and low light on growth rate. Low iron treatments (saturating and low light) had the largest transcriptomic response; however, expression patterns were more similar in low light treatments (high and low iron). Under iron and light limitation, carbon fixation and amino acid, ribosome, and sulfur metabolisms were overrepresented relative to the control (iron replete, saturating light). Transcripts of genes encoding for the proteins aquaporin, proteorhodopsin, plastocyanin, and flavodoxin were overrepresented to the greatest extent in the low iron/low light treatment, indicating there may be an additive effect of iron/light colimitation at the molecular level. Iron and light replete cells demonstrated increased expression of genes encoding for the proteins ferritin, carbonic anhydrase, and numerous iron‐dependent proteins relative to the growth‐limiting treatments. This transcriptome analysis reveals mechanisms that may underpin the ecological success of this diatom in low iron and light environments, highlighting the important role of diversified photosynthetic isoforms, iron acquisition, unique detoxification mechanisms of reactive oxygen species, and metabolic shifts in amino acid recycling and carbon metabolism.

Phase I pharmacological study of continuous chronomodulated capecitabine treatment - Jeroen Roosendaal; Bart A. W. Jacobs; Dick Pluim; Hilde Rosing; Niels de Vries; Erik van Werkhoven; Bastiaan Nuijen; Jos H. Beijnen; Alwin D. R. Huitema; Jan H. M. Schellens; Serena Marchetti (Pharmaceutical Research, 2020)
Purpose Capecitabine is an oral pre-pro-drug of the anti-cancer drug 5-fluorouracil (5-FU). The biological activity of the 5-FU degrading enzyme, dihydropyrimidine dehydrogenase (DPD), and the target enzyme thymidylate synthase (TS), are subject to circadian rhythmicity in healthy volunteers. The aim of this study was to determine the maximum tolerated dose (MTD), dose-limiting toxicity (DLT), safety, pharmacokinetics (PK) and pharmacodynamics (PD) of capecitabine therapy adapted to this circadian rhythm (chronomodulated therapy). Methods Patients aged ≥18 years with advanced solid tumours potentially benefitting from capecitabine therapy were enrolled. A classical dose escalation 3 + 3 design was applied. Capecitabine was administered daily without interruptions. The daily dose was divided in morning and evening doses that were administered at 9:00 h and 24:00 h, respectively. The ratio of the morning to the evening dose was 3:5 (morning: evening). PK and PD were examined on treatment days 7 and 8. Results A total of 25 patients were enrolled. The MTD of continuous chronomodulated capecitabine therapy was established at 750/1250 mg/m 2 /day, and was generally well tolerated. Circadian rhythmicity in the plasma PK of capecitabine, dFCR, dFUR and 5-FU was not demonstrated. TS activity was induced and DPD activity demonstrated circadian rhythmicity during capecitabine treatment. Conclusion The MTD of continuous chronomodulated capecitabine treatment allows for a 20% higher dose intensity compared to the approved regimen (1250 mg/m 2 bi-daily on day 1–14 of every 21-day cycle). Chronomodulated treatment with capecitabine is promising and could lead to improved tolerability and efficacy of capecitabine.

On the presence of Ichniotherium in the Coconino Sandstone (Cisuralian) of the Grand Canyon and remarks on the occupation of deserts by non-amniote tetrapods - Heitor Francischini; Spencer G. Lucas; Sebastian Voigt; Lorenzo Marchetti; Vincent L. Santucci; Cassandra L. Knight; John R. Wood; Paula Dentzien-Dias; Cesar L. Schultz (PalZ, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

The iron limitation mosaic in the California Current System: Factors governing Fe availability in the shelf/near‐shelf region - C. P. Till; J. R. Solomon; N. R. Cohen; R. H. Lampe; A. Marchetti; T. H. Coale; K. W. Bruland (Limnology and Oceanography, 2019)
The California Current System is a productive eastern boundary region off the coasts of Washington, Oregon, and California. There is strong seasonality to the region, with high levels of rainfall and river input to the coastal ocean during the winter season, and coastal and Ekman upwelling during the spring and summer. Iron (Fe) input to the coastal ocean during the winter months can be stored in the continental shelf mud belts and then be delivered to the surface ocean by upwelling in the spring and summer. There have been a number of studies providing strong evidence of Fe‐limitation of diatom growth occurring in regions of the California Current System off of California, and the occurrence of Fe‐limitation has been linked with narrow continental shelf mud belt width and low river input. We provide evidence for potential Fe‐limitation of diatoms off the southern coast of Oregon in July 2014, just off the shelf break near Cape Blanco in a region with moderate shelf width and river input. Since eastern boundary regions account for a disproportionally large amount of global primary production, this observation of potential Fe‐limitation in an unexpected near‐shore region of the California Current System has implications for global models of primary productivity. In order to re‐evaluate the factors impacting Fe availability, we utilize satellite imagery to compare with historical datasets, and show that unexpected levels of Fe can often be explained by eddies, plumes of upwelled water moving offshore, or lack of recent upwelling.

Transcriptomic and proteomic responses of the oceanic diatom Pseudo‐nitzschia granii to iron limitation - Natalie R Cohen; Weida Gong; Dawn M. Moran; Matthew R. McIlvin; Mak A. Saito; Adrian Marchetti (Environmental Microbiology, 2018)
Summary Diatoms are a highly successful group of photosynthetic protists that often thrive under adverse environmental conditions. Members of the genus Pseudo‐nitzschia are ecologically important diatoms which are able to subsist during periods of chronic iron limitation and form dense blooms following iron fertilization events. The cellular strategies within diatoms that orchestrate these physiological responses to variable iron concentrations remain largely uncharacterized. Using a combined transcriptomic and proteomic approach, we explore the exceptional ability of a diatom isolated from the iron‐limited Northeast Pacific Ocean to reorganize its intracellular processes as a function of iron. We compared the molecular responses of Pseudo‐nitzschia granii observed under iron‐replete and iron‐limited growth conditions to those of other model diatoms. Iron‐coordinated molecular responses demonstrated some agreement between gene expression and protein abundance, including iron‐starvation‐induced‐proteins, a putative iron transport system and components of photosynthesis and the Calvin cycle. Pseudo‐nitzschia granii distinctly differentially expresses genes encoding proteins involved in iron‐independent photosynthetic electron transport, urea acquisition and vitamin synthesis. We show that P. granii is unique among studied diatoms in its physiology stemming from distinct cellular responses, which may underlie its ability to subsist in low iron regions and rapidly bloom to outcompete other diatom taxa following iron enrichment.

Divergent gene expression among phytoplankton taxa in response to upwelling - Robert H. Lampe; Natalie R. Cohen; Kelsey A. Ellis; Kenneth W. Bruland; Maria T. Maldonado; Tawnya D. Peterson; Claire P. Till; Mark A. Brzezinski; Sibel Bargu; Kimberlee Thamatrakoln; Fedor I Kuzminov; Benjamin S. Twining; et al. (Environmental Microbiology, 2018)
Summary Frequent blooms of phytoplankton occur in coastal upwelling zones creating hotspots of biological productivity in the ocean. As cold, nutrient‐rich water is brought up to sunlit layers from depth, phytoplankton are also transported upwards to seed surface blooms that are often dominated by diatoms. The physiological response of phytoplankton to this process, commonly referred to as shift‐up, is characterized by increases in nitrate assimilation and rapid growth rates. To examine the molecular underpinnings behind this phenomenon, metatranscriptomics was applied to a simulated upwelling experiment using natural phytoplankton communities from the California Upwelling Zone. An increase in diatom growth following 5 days of incubation was attributed to the genera Chaetoceros and Pseudo‐nitzschia . Here, we show that certain bloom‐forming diatoms exhibit a distinct transcriptional response that coordinates shift‐up where diatoms exhibited the greatest transcriptional change following upwelling; however, comparison of co‐expressed genes exposed overrepresentation of distinct sets within each of the dominant phytoplankton groups. The analysis revealed that diatoms frontload genes involved in nitrogen assimilation likely in order to outcompete other groups for available nitrogen during upwelling events. We speculate that the evolutionary success of diatoms may be due, in part, to this proactive response to frequently encountered changes in their environment.

Iron storage capacities and associated ferritin gene expression among marine diatoms - Natalie R. Cohen; Elizabeth Mann; Brooke Stemple; Carly M. Moreno; Sara Rauschenberg; Jeremy E. Jacquot; William G. Sunda; Benjamin S. Twining; Adrian Marchetti (Limnology and Oceanography, 2018)
In large regions of the ocean, low iron availability regulates diatom growth and species composition. Diatom species often vary in their physiological response to iron enrichment, with natural and artificial iron additions in iron‐limited regions of the ocean resulting in large blooms of primarily pennate diatoms. The ability of pennate diatoms to proliferate following pulse iron additions has been partly attributed to their ability to acquire and store excess intracellular iron in the iron storage protein ferritin. Recent transcriptome sequencing of diatoms indicate that some centric diatoms also possess ferritin. Using a combination of physiological and molecular techniques, we examined the iron storage capacities and associated ferritin gene expression in phylogenetically diverse centric and pennate diatoms grown under high and low iron concentrations. There were no systematic differences among ferritin‐containing and non‐containing diatom lineages in their ability to store iron in excess of that needed to support maximum growth rates. An exception, however, was the ferritin‐containing pennate diatom Pseudo‐nitzschia granii , native to iron‐limited waters of the Northeast Pacific Ocean. This species exhibited an exceptionally large luxury iron storage capacity and increased ferritin gene expression at high iron concentrations, supporting a role in long‐term iron storage. By contrast, two other diatoms species that exhibited minimal iron storage capacities contained two distinct ferritin genes where one ferritin gene increased in expression under iron limitation while the second showed no variation with cellular iron status. We conclude that ferritin may serve multiple functional roles that are independent of diatom phylogeny.

An updated checklist of the vascular flora alien to Italy - G. Galasso; F. Conti; L. Peruzzi; N. M. G. Ardenghi; E. Banfi; L. Celesti-Grapow; A. Albano; A. Alessandrini; G. Bacchetta; S. Ballelli; M. Bandini Mazzanti; G. Barberis; et al. (Plant Biosystems, 2018)

Corrigendum: Diatom Transcriptional and Physiological Responses to Changes in Iron Bioavailability across Ocean Provinces - Natalie R. Cohen; Kelsey A. Ellis; Robert H. Lampe; Heather McNair; Benjamin S. Twining; Maria T. Maldonado; Mark A. Brzezinski; Fedor I. Kuzminov; Kimberlee Thamatrakoln; Claire P. Till; Kenneth W. Bruland; William G. Sunda; et al. (Frontiers in Marine Science, 2018)

An updated checklist of the vascular flora native to Italy - F. Bartolucci; L. Peruzzi; G. Galasso; A. Albano; A. Alessandrini; N. M. G. Ardenghi; G. Astuti; G. Bacchetta; S. Ballelli; E. Banfi; G. Barberis; L. Bernardo; et al. (Plant Biosystems, 2018)

Toward an Improved Representation of Middle Atmospheric Dynamics Thanks to the ARISE Project - E. Blanc; L. Ceranna; A. Hauchecorne; A. Charlton-Perez; E. Marchetti; L. G. Evers; T. Kvaerna; J. Lastovicka; L. Eliasson; N. B. Crosby; P. Blanc-Benon; A. Le Pichon; et al. (Surveys in Geophysics, 2018)

Diatom Transcriptional and Physiological Responses to Changes in Iron Bioavailability across Ocean Provinces - Natalie R. Cohen; Kelsey A. Ellis; Robert H. Lampe; Heather McNair; Benjamin S. Twining; Maria T. Maldonado; Mark A. Brzezinski; Fedor I. Kuzminov; Kimberlee Thamatrakoln; Claire P. Till; Kenneth W. Bruland; William G. Sunda; et al. (Frontiers in Marine Science, 2017)
Changes in iron (Fe) bioavailability influence diatom physiology and community composition, and thus have a profound impact on primary productivity and ecosystem dynamics. Iron limitation of diatom growth rates has been demonstrated in both oceanic and coastal waters of the Northeast Pacific Ocean and is predicted to become more pervasive in future oceans. However, it is unclear how the strategies utilized by phytoplankton to cope with low Fe bioavailability and resupply differ across these ocean provinces. We investigated the response of diatom communities to variable Fe conditions through incubation experiments performed in the Fe mosaic of the California Upwelling Zone and along a natural Fe gradient in the Northeast Pacific Ocean. Through coupling gene expression of two dominant diatom taxa ( Pseudo-nitzschia and Thalassiosira ) with biological rate process measurements, we provide an in-depth examination of the physiological and molecular responses associated with varying Fe status. Following Fe enrichment, oceanic diatoms showed distinct differential expression of gene products involved in nitrogen assimilation, photosynthetic carbon fixation, and vitamin production compared to diatoms from low-Fe coastal sites, possibly driven by the chronic nature of Fe stress at the oceanic site. Genes of interest involved in Fe and N metabolism additionally exhibited divergent expression patterns between the two diatom taxa investigated, demonstrating that diverse diatoms may invoke alternative strategies when dealing with identical changes in their environment. We report here several mechanisms used distinctly by coastal or oceanic diatom communities as well as numerous taxa-specific strategies for coping with Fe stress and rearranging nutrient metabolism following Fe enrichment.

Iron and vitamin interactions in marine diatom isolates and natural assemblages of the Northeast Pacific Ocean - Natalie R. Cohen; Kelsey A. Ellis; Wilton G. Burns; Robert H. Lampe; Nina Schuback; Zackary Johnson; Sergio Sañudo‐Wilhelmy; Adrian Marchetti (Limnology and Oceanography, 2017)
Trace metals and B‐vitamins play critical roles in regulating marine phytoplankton growth and composition. While some microorganisms are capable of producing certain B‐vitamins, others cannot synthesize them and depend on an exogenous supply. Therefore, external factors influencing vitamin synthesis, such as micronutrient concentrations, alter the extent to which B‐vitamins are available to auxotrophs in surface waters. We examined iron, B 7 (biotin) and B 12 (cobalamin) dynamics in diatoms through laboratory culture experiments and within natural diatom assemblages present along an iron gradient in the Northeast Pacific Ocean. In laboratory cultures of the diatom Pseudo‐nitzschia granii , biotin synthase (BIOB ) expression decreased 2‐fold under iron limitation, suggesting iron status may affect B 7 production in diatoms. Additionally in laboratory cultures of the diatom Grammonema cf. islandica , which contains a B 12 ‐independent methionine synthase ( METE ), a 15‐fold increase in the expression of METE was observed when grown in the absence of B 12 with no significant influence of iron status, suggesting METE expression can be driven by B 12 status alone. Iron and B‐vitamin amendment experiments with natural diatom assemblages in iron‐limited waters of the Northeast Pacific Ocean provide evidence for vitamin‐associated molecular responses that suggest elevated B 7 biosynthesis and the emergence of B 12 limitation following iron addition. Furthermore B‐vitamin gene modules comprised of partial and/or complete B‐vitamin biosynthetic pathways in diatoms increased in response to iron addition, including genes potentially involved in the processing of B 12 intermediates. Our results indicate that vitamins may play an important role in regulating phytoplankton growth and composition in this region, particularly following natural iron addition events.

The influence of slope on Spartium junceum root system: morphological, anatomical and biomechanical adaptation - Fabio Lombardi; G. S. Scippa; B. Lasserre; A. Montagnoli; R. Tognetti; M. Marchetti; D. Chiatante (Journal of Plant Research, 2017)

Streptococcus salivarius by nasal spray for recurrent otitis: how good is the evidence? - S. Di Mario; V. Basevi; R. D’Amico; C. Gagliotti; M. Gangemi; F. Marchetti; M. L. Moro; G. Tamburlini (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

CSF lactate for accurate diagnosis of community-acquired bacterial meningitis - S. Giulieri; C. Chapuis-Taillard; K. Jaton; A. Cometta; C. Chuard; O. Hugli; R. Du Pasquier; J. Bille; P. Meylan; O. Manuel; O. Marchetti (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Three new hybrids of Ophioglossum (Ophioglossaceae) from Monte Pisano, Tuscany (Central Italy) - L. Peruzzi; B. Pierini; S. Magrini; A. Andreucci; D. Marchetti; R. Viane (Plant Biosystems, 2015)

Mountain vegetation at risk: Current perspectives and research reeds - C. Palombo; M. Marchetti; R. Tognetti (Plant Biosystems, 2014)

Is land abandonment affecting forest dynamics at high elevation in Mediterranean mountains more than climate change? - C. Palombo; G. Chirici; M. Marchetti; R. Tognetti (Plant Biosystems, 2013)

Carbon sequestration by forests in the National Parks of Italy - M. Marchetti; L. Sallustio; M. Ottaviano; A. Barbati; P. Corona; R. Tognetti; L. Zavattero; G. Capotorti (Plant Biosystems, 2012)

A CAD/CAM-prototyped anatomical condylar prosthesis connected to a custom-made bone plate to support a fibula free flap - L. Ciocca; S. Mazzoni; M. Fantini; F. Persiani; P. Baldissara; C. Marchetti; R. Scotti (Medical & Biological Engineering & Computing, 2012)

Do National Parks play an active role in conserving the natural capital of Italy? - G. Capotorti; L. Zavattero; I. Anzellotti; S. Burrascano; R. Frondoni; M. Marchetti; M. Marignani; D. Smiraglia; C. Blasi (Plant Biosystems, 2012)

Comparison of forest stand structure and management of silver fir–European beech forests in the Central Apennines, Italy and in the Dinaric Mountains, Slovenia - F. Lombardi; M. Klopcic; P. Di Martino; R. Tognetti; G. Chirici; A. Boncina; M. Marchetti (Plant Biosystems, 2012)

What’s the catch? Patterns of cetacean bycatch and depredation in Hawaii‐based pelagic longline fisheries - Karin A. Forney; Donald R. Kobayashi; David W. Johnston; Jamie A. Marchetti; Michael G. Marsik (Marine Ecology, 2011)
U.S. Pacific pelagic longline fisheries operating in the central North Pacific have been subject to a series of regulations to reduce bycatch of protected species, including seabirds and sea turtles. Cetaceans are also occasionally caught, and the bycatch of false killer whales, Pseudorca crassidens , in the Hawaii‐based deep‐set longline fishery currently exceeds allowable levels under the Marine Mammal Protection Act (MMPA). In this study, we examined longline observer data collected between 1994 and 2009, with emphasis on 2003–2009, to identify patterns of cetacean bycatch and depredation in relation to area, time, vessel, habitat variables, fishing gear, and set characteristics. The objectives of these analyses were to identify relationships amongst fishery interaction rates and variables that could provide opportunities to reduce depredation by cetaceans, reduce the likelihood of incidentally catching a cetacean when present, or reduce the severity of injuries to cetaceans if caught. The results of this study were provided to the False Killer Whale Take Reduction Team, convened under the MMPA, as they developed a plan to reduce serious injury and mortality of false killer whales in these fisheries. No correlates were identified that could markedly reduce depredation rates, but a slight (16%) reduction in repeat depredation within a fishing trip was evident when vessels moved at least 100 km following a depredation event. The most practical option for reducing bycatch of false killer whales was determined to be the use of small (14/0–16/0) circle hooks, which could result in an estimated 6% reduction in bycatch and a greater likelihood of releasing animals with non‐serious injuries. Additional research is needed to address unresolved questions relating to processes involved in depredation events and hookings or entanglements of false killer whales.

Ecological portrayal of old‐growth forests and persistent woodlands in the Cilento and Vallo di Diano National Park (southern Italy) - M. Marchetti; R. Tognetti; F. Lombardi; U. Chiavetta; G. Palumbo; M. Sellitto; C. Colombo; P. Iovieno; A. Alfani; D. Baldantoni; A. Barbati; B. Ferrari; et al. (Plant Biosystems, 2010)

Patterns and trends in tropical forest cover - R. Drigo; B. Lasserre; M. Marchetti (Plant Biosystems, 2009)

Progenitor cells and retinal angiogenesis - Martin Friedlander; Michael I. Dorrell; Matthew R. Ritter; Valentina Marchetti; Stacey K. Moreno; Mohammad El-Kalay; Alan C. Bird; Eyal Banin; Edith Aguilar (Angiogenesis, 2007)

Microbial Reductive Dechlorination of Weathered and Exogenous Co-planar Polychlorinated Biphenyls (PCBs) in an Anaerobic Sediment of Venice Lagoon - G. Zanaroli; J. R. Pérez-Jiménez; L. Y. Young; L. Marchetti; F. Fava (Biodegradation, 2006)

Bacteriostatic and bactericidal activity of levofloxacin against clinical isolates from cystic fibrosis patients - G. Golini; F. Favari; F. Marchetti; R. Fontana (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Mapping QTLs for field resistance to the rice blast pathogen and evaluating their individual and combined utility in improved varieties - R. Tabien; Z. Li; A. Paterson; M. Marchetti; J. Stansel; S. Pinson (Theoretical and Applied Genetics, 2002)

Mapping of four major rice blast resistance genes from ’Lemont’ and ’Teqing’ and evaluation of their combinatorial effect for field resistance - R. E. Tabien; Z. Li; A. H. Paterson; M. A. Marchetti; J. W. Stansel; S. R. M. Pinson; W. D. Park (Theoretical and Applied Genetics, 2000)

The effect of urea and pig slurry fertilization on denitrification, direct nitrous oxide emission, volatile fatty acids, water-soluble carbon and anthrone-reactive carbon in maize-cropped soil from the Po plain (Modena, Italy) - P. G. Arcara; C. Gamba; D. Bidini; R. Marchetti (Biology and Fertility of Soils, 1999)